THE APPLICATION OF DEBATE TEACHING TECHNIQUES TO IMPROVE STUDENT SPEAKING ABILITY AT CLASS XI ATPH OF SMK-PP NEGERI KUTACANE IN ACADEMIC YEAR 2022/2023 - Miftahun Jannah; RAJA FAUZIAH; Abdul Halim (STKIP USMAN SAFRI KUTACANE, 2024)
This study deal with the application of debate teaching techniques to improve student speaking ability at class XI ATPH of smk-pp negeri kutacane in academic year 2022/2023. Its objective is to find out whether the application debate teaching techniques can improve student speaking ability. Population used in this study of class xi ATPH and xi BUN were 64 student and sample used in this study of class XI ATPH were 33 student. The methode used in this study is an exsperimental method with a make pre-test and post-test design. This study carried on using quantitative method. The data was analysed by using t-test. The reseacher found the pre-test mean = 55,45, standart deviation = 7,21 and experienced an increase in the post-test mean = 73,33, standart deviation = 5,59. From this analysis, writer found that debate teaching techniques can improve student speaking ability. It can be proved by the result of the analysis showed that “to” observed about 33,74 was higher then “ttable” about 2,037 with level alpha 5%. Its implies that english teacher can application debate teaching techniques to improve student speaking ability. So that the teaching and learning process can be successfull.